2020
DOI: 10.1186/s12879-020-05252-8
|View full text |Cite
|
Sign up to set email alerts
|

Clinical characteristics of 276 hospitalized patients with coronavirus disease 2019 in Zengdu District, Hubei Province: a single-center descriptive study

Abstract: Background: We aimed to report the epidemiological and clinical characteristics of hospitalized patients with coronavirus disease-19 (COVID-19) in Zengdu District, Hubei Province, China. Methods: Clinical data on COVID-19 inpatients in Zengdu Hospital from January 27 to March 11, 2020 were collected; this is a community hospital in an area surrounding Wuhan and supported by volunteer doctors. All hospitalized patients with COVID-19 were included in this study. The epidemiological findings, clinical features, l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 28 publications
(32 reference statements)
2
39
0
Order By: Relevance
“…In studies which reported BMI, we observed higher rates of obesity (BMI�30kg/m 2 ) in patients with severe disease (OR = 1.89, 95% CI: 1.44-2.46; I 2 = 0.0%) [20,21,23,26,30,35]. [26,28,35,38,45] showed no significant differences between patients with severe and non-severe disease.…”
Section: Demographic Characteristicsmentioning
confidence: 55%
“…In studies which reported BMI, we observed higher rates of obesity (BMI�30kg/m 2 ) in patients with severe disease (OR = 1.89, 95% CI: 1.44-2.46; I 2 = 0.0%) [20,21,23,26,30,35]. [26,28,35,38,45] showed no significant differences between patients with severe and non-severe disease.…”
Section: Demographic Characteristicsmentioning
confidence: 55%
“…There are 2471 patients from 14 studies included in this systematic review and meta-analysis [ [6] , [7] , [8] , [9] , [10] , [11] , [12] , [13] , [14] , [15] , [16] , [17] , [18] , [19] ]. The baseline characteristics of the included studies can be accessed in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
“…Most studies were from China 5 , 9 , 11 , 16 38 ( n = 26), followed by United States 39 43 ( n = 5), Switzerland 44 , 45 ( n = 2), Japan 8 ( n = 1), Korea 46 ( n = 1), Oman 47 ( n = 1), Qatar 48 ( n = 1), Iran 49 ( n = 1), Denmark 50 ( n = 1), Mexico 51 ( n = 1), and Bulgaria 52 ( n = 1). The sample size of included studies ranged from 41 to 5000 patients.…”
Section: Resultsmentioning
confidence: 99%